Buscando héroes: la historia de Antonio Col como ejemplo del uso de la narrativa como propaganda durante la Guerra Civil española - Cabeza San Deogracias, José (Historia y Comunicación Social, 2005)
This article studies how a propaganda campaign was built to reach a very concrete and limited aim: to raise the number of voluntaries to act as anti-tanquer —antitanquista— in the republican army in Madrid. In order to get this target, propaganda pushed forward a plan to make a legend about a local hero, Antonio Col, reproducing a narrative scheme showed in a soviet film sequence: Los marinos de Cronstadt (Dzigan - G. Berenko, 1936). Soviet films were barely popular in the theatres but, paradoxically, Los marinos de Cronstadt was very useful in this very specific case. This article also analyzes the context of the exhibition of soviet revolutionary movies and, finally, thinks over the use of the narrative as propaganda and its influence in the creation of anti-tanquer phenomenon.
Keywords: narrative / propaganda / Spanish Civil War / cinema